Pendampingan Keterampilan Manajeman Data Kesehatan Kaum Marginal pada LKC Dompet Dhuafa Jakarta - Laras Sitoayu; Lintang Purwara Dewanti; Nanda Aula Rumana; Lutfi Fanani; Edi Hamdi; Dian Puspita Sari; Putri Azahra Sumitra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The distribution of disadvantaged groups in need of health services is increasing every year. The government's BPJS program cannot be fully followed by the marginalized. Therefore, we need NGOs that care about the health of marginalized people, like the LKC Dompet Dhuafa service. Every month, hundreds of medical services are successfully provided by Dompet Dhuafa, but medical data management is not done optimally. The purpose of this activity is to support health data management of marginalized people in areas under the leadership of Dhuafa Wallet as an innovation to promote teamwork in the field. Methods to support this activity include 1) Improve knowledge of data management and medical record keeping, and 2) Create a health information system for disadvantaged groups. The target of this activity is 8 volunteers. Based on the evaluation results, volunteers' knowledge increased from an average score of 60 to 80. It is hoped that this health data management support will fill the gap and improve health services for disadvantaged groups.